10° off-axis testing of CFRP using DIC: A study on strength, strain and modulus. (1st September 2020) - Merzkirch, Matthias; Foecke, Tim
Abstract: For the determination of the shear properties such as strength, strain and modulus of unidirectionally reinforced composites, nearly a dozen measurement techniques exist, several of which have found their way into standards. One non-standardized method for sheet materials is the 10° off-axis tensile test of unidirectional coupons. The current work focuses on the experimental investigation of tensile testing of CFRP-UD coupon specimens using the 10° off-axis test and DIC strain mapping to measure the full-field deformation response. A sensitivity analysis on the measured stresses, strains and moduli is performed by varying the aspect ratio of the specimens and the location of strain measurement. Test related uncertainties such as the loading angle and specimen preparation details are investigated and quantified with the help of these full-field DIC measurements.